Design, modeling, and experimental evaluation of a self-sealing component for rotary shafts in magneto-rheological fluid devices - Cuong, Vo Van; Nguyen, Quoc Hung; Zy, Le Hai Zy; Nguyen, Ngoc Diep; Tuan, Le Duy; Hieu, Do Huu Minh; Duyen, Do Quy (Vietnam Journal of Mechanics, 2023)
This study focuses on the development and evaluation of a self-sealing component for rotary shafts in Magneto-rheological (MR) fluid-based devices, such as MR brakes and MR clutches. The proposed sealing component, which replaces traditional lip-seals, consists of a permanent magnet and a magnetic core positioned on the rotary shaft. Through a combination of simulation and experimentation, the design and performance of the self-sealing component are investigated. Initially, the research provides an overview of MR fluid and its applications, as well as previous studies on sealing components utilizing MR fluid. Building on this background, a configuration for the self-sealing component specific to rotary shafts in MR fluid-based devices is proposed. The design and modeling of the sealing component are carried out, employing the Bingham plastic rheological model of the MR fluid and finite element analysis techniques. Through finite element analysis, an optimal design for the sealing component is determined. Prototypes of the sealing component are manufactured, and experimental testing is conducted to assess its performance characteristics. The experimental results are then compared with the simulated results, allowing for a comprehensive evaluation of the sealing component’s effectiveness.